ANALYSIS OF CHANGES IN COASTLINES IN DISTRICT OF BANGKALAN MADURA WITH GEOGRAPHIC INFORMATION SYSTEM APPROACH AND LANDSAT 8 SATELLITE IMAGERY - Farihatul Islamiyah; Hendrata Wibisana (Journal of Civil Engineering Science and Technology (CI-TECH), 2020)
The coastline is the meeting area between land and sea. In this area, many are influenced by various natural factors and also human activities, where changes that occur such as climatological effects will have an impact on the existing coastline, as well as human activities in the coastal areas will have an impact on the morphological form of the coast including in it the coastline. This study intends to see which mathematical model is most suitable for describing the changes that have occurred and also to measure how much change occurs each year. The method used in this research is spatial analysis using a geographic information system which is used to analyse the Landsat 8 OLI satellite image of the coastline in Bangkalan Madura district, and to measure satellite imagery for a period of 5 years from 2016 to 2020. The results obtained from this study, the polynomial mathematical model is the most suitable model to describe the process of change, where this model provides maximum results with a significant correlation value of 0.8107 for degree 2 and 0.9323 for degree polynomial 3. From this study It can be concluded that Landsat 8 satellite imagery is suitable for data collection on shoreline changes because this satellite image has sufficient resolution to describe in detail the length of the coastline under study. Changes in the coastline that occur are not linear, but throughout the year there are fairly dynamic changes to the shoreline, both in terms of a shoreline retreat or an addition to the coastline.